Problemas familiares que afectan en el rendimiento académico - Castillo Barraquel, Diana Elizabeth (2017)
In the Domingo Faustino Sarmiento School, in Pelileo cantón, with students the third year of Basic General Education, afterward applying a survey to the students, parents and teachers, the results have evidenced that the family issues affect the good development of the educative performance in students. Furthermore, it was stablished that exists some factors that limit the overcoming capabilities on the good school performance. It is well described in the following aspects: inadequate feeding, family formation, physical and emotional abuse, congenital problems and so on. The increasing level of family issues has produce an alarming number of formal and practical separations, besides disagreement between spouses and families, talking about education and unemployment toward their sons and daughters; consequently, as a result they do not take responsibility and care of their rights and obligations leading them even to the death. It obviously is reflected in the personality of the students provoking social incommunication, it is evidenced on the quantitative, qualitative and behavioral grades.